Investigation of inflammatory markers after electrostimulation - Crabtree, Daniel (Acta Biologica Szegediensis, 2013)
Electric and magnetic fields are known to interact with living systems. Our aim was to determine the impact of electric stimulation on human immune cells at the level of gene expression. THP-1 human monocytes were treated with direct electric impulses and with the electric field of a commercial cell phone. The relative expression of 21 genes was determined by real-time quantitative PCR and calculated by ΔΔCt method with GAPDH control. The smaller electric field and electromagnetic field of cell phone have a slight, not significant but consequent down-regulation of the pro-inflammatory genes. The higher electric field induced significant up-regulation of same genes.